Reference Values Matter: Fewer Patients With Malnutrition Using American Compared to More Recent German Growth Charts. Issue 6 (June 2021) - Ellemunter, Helmut; Dumke, Markus; Steinkamp, Gratiana
Abstract : ABSTRACT: Reference values are important for patient care as well as for comparisons between different centers or countries. We investigated two anthropometric reference datasets, the US Centers for Disease Control (CDC) growth charts and the German Health Interview and Examination Survey for Children and Adolescents Study (KiGGS) percentiles, which were established in Germany between 2003 and 2006. A smaller proportion of children with cystic fibrosis had decreased z scores <−2 with CDC (5.0% for weight and 3.0% for height) compared to KiGGS (7.4% for weight and 6.3% for height) values ( P < 0.0001). Median z scores were higher using the CDC reference data. Thus, the choice of growth reference is important, may influence clinical management and must be considered when comparing the outcomes of different institutions.